Derrida at the Multiplex: Why Deconstruction Disconcerts the Philosophical Establishment - Rajagopalan, Kanavillil (Revista de Letras, 2009)
Focusing largely on the debate in the philosophy of language between Searle and Derrida on the subject of speech act theory, this essay reveals a fundamental impasse between textualist (or deconstructive) and systematic (or philosophical) reading. It asserts that deconstruction’s insistence on the irreducible heterogeneity and plurality of textual meaning renders it inassimilable within the more homogenizing systems of meaning that are dominant within the philosophical establishment. For Rajagopalan the legacy of deconstruction is constituted, at least in part, by this ongoing resistance to assimilation within the philosophical mainstream. Keywords: Speech act theory. Performativity. Textualism. Searle. Heterology. Platonism.